Advocacy Without Adversity: Developing an Understanding of Micropolitical Theory to Promote a Comprehensive School Counseling Program. Issue 1 (8th April 2021) - Oehrtman, Jeremy P.; Dollarhide, Colette T.
School counselors are urged to create systemic change within a school system by working as an advocate, leader, and collaborator within the school. Each of these roles requires a school counselor to be skilled in micropolitics and micropolitical literacy. This article explores the main concepts of micropolitical theory and its application to the school counseling profession. We also discuss the limitations and implications of this position.